2011
DOI: 10.1002/jcc.21975
|View full text |Cite
|
Sign up to set email alerts
|

Direct evaluation of individual hydrogen bond energy in situ in intra‐ and intermolecular multiple hydrogen bonds system

Abstract: The results of evaluating the individual hydrogen bond (H-bond) strength are expected to be helpful for the rational design of new strategies for molecular recognition or supramolecular assemblies. Unfortunately, there is few obvious and unambiguous means of evaluating the energy of a single H-bond within a multiple H-bonds system. We present a local analytic model, ABEEMσπ H-bond energy (HBE) model based on ab initio calculations (MP2) as benchmark, to directly and rapidly evaluate the individual HBE in situ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 101 publications
(136 reference statements)
0
14
0
Order By: Relevance
“…Wilson and Ichikawa and Torrent‐Sucarrat and coworkers pointed out that the charge transfer between atoms in a molecule is overestimated by using the polarization basis sets. Huzinaka et al, Jakalian et al, Watanabe et al, and our group have shown that the use of higher levels of basis sets overestimates the overlap between their respective basis functions belonging to two atoms in a molecule. Bayly and his coworkers pointed out that when the 6‐31G* basis set is used, the polarity of a molecule calculated by the partial charges is overestimated by 10%–15% .…”
Section: Computational Detailsmentioning
confidence: 66%
“…Wilson and Ichikawa and Torrent‐Sucarrat and coworkers pointed out that the charge transfer between atoms in a molecule is overestimated by using the polarization basis sets. Huzinaka et al, Jakalian et al, Watanabe et al, and our group have shown that the use of higher levels of basis sets overestimates the overlap between their respective basis functions belonging to two atoms in a molecule. Bayly and his coworkers pointed out that when the 6‐31G* basis set is used, the polarity of a molecule calculated by the partial charges is overestimated by 10%–15% .…”
Section: Computational Detailsmentioning
confidence: 66%
“…Wilson and Ichikawa and Torrent‐Sucarrat et al pointed out that the charge transfer between atoms in a molecule is overestimated when the polarization basis sets are used. Huzinaka et al, Jakalian et al, and Watanabe et al as well as our group , had experienced that the use of higher level of basis sets overestimates the overlap between their respective basis functions belonging to two atoms in a molecule. Bayly and coworkers pointed out that the 6–31G* basis set is used, the polarity of a molecule calculated by the partial charges is overestimated by 10–15% used .…”
Section: Calibration Of the Parametersmentioning
confidence: 77%
“…, and q O(OH − ) * are the valence-state energy, valence-state electronegativity, valence-state hardness, and initial charge 117 particle N, volume V, and temperature T) conditions at 298 and 278 K; temperature was kept constant by Berendsen algorithm. 130 Periodic boundary condition was applied in all three dimensions.…”
Section: Theoretical Models and Computational Methodsmentioning
confidence: 99%
“…A QM calculation with a higher level of basis set can give more accurate predictions of energy and geometry, but it cannot give more suitable partial charges than the lower level of basis set for practical use. Because a diffuse basis function located on an atom may to some extent cover the regions of the other adjacent atoms, it will lead to a somewhat overestimating population of this atom in the Mulliken population analysis . Derouane and his co-workers suggested that STO-3G charges are more reliable.…”
Section: Theoretical Models and Computational Methodsmentioning
confidence: 99%